Effect of interfacial surface treatment on bond strength of particulate-filled composite to short fiber-reinforced composite - Tuokko, Jarno (My University, 2022)
Abstract Objective: The aim was to investigate the effect of different interfacial surface treatments on the shear bond strength (SBS) between short fiber-reinforced flowable composite (SFRC) and a particulate-filled flowable composite (PFC). In addition, SBS between two successive layers of similar materials was evaluated. Materials and methods: One-hundred and forty-four specimens were prepared having either SFRC (everX Flow) as substructure composite and PFC (G-aenial Flo X) as surface composite or having one of the two materials as both substructure and surface layer. Eight groups of specimens were created (n=18/per group) according to the interfacial surface protocol used. Group 1: no treatment; Group 2: ethanol one wipe; Group 3: ethanol three wipes; Group 4: phosphoric acid etching + bonding agent; Group 5: hydrofluoric acid etching + bonding agent; and Group 6: grinding + phosphoric acid etching. Group 7: only PFC layers and Group 8 (control) only SFRC layers without any surface treatment. After one-day storage (37 °C) SBS between surface and substructure composite layers was measured in a universal testing machine, and failure modes were visually analyzed. SEM was used to examine the bonding surface of the SFRC composite after surface treatment. SBS values were statistically analyzed with a one-way analysis of variance (ANOVA) followed by Tukey HSD test (α=.05). Results: The SBS between successive SFRC layers (Group 8) was statistically (p<0.05) the highest (43.7 MPa) among tested groups. Surface roughening by grinding followed by phosphoric acid etching (Group 6) resulted in a higher SBS (28.8 MPa) than the remaining surface treatments. Conclusion: Flowable composite with glass fibers (everX Flow) showed higher interlayer SBS compared to PFC flowable composite. Interfacial surface roughness increases the bonding of PFC to the substructure of SFRC. Keywords: Short-fiber reinforced composite, surface treatment, flowable composite, shear bond strength
Keywords: Short-fiber reinforced composite, surface treatment, flowable composite, shear bond strength